Serum matrix metalloproteinase‐7, Syndecan‐1, and CA 19‐9 as a biomarker panel for diagnosis of pancreatic ductal adenocarcinoma - Doron Yablecovitch; Moshe Nadler; Shomron Ben‐Horin; Orit Picard; Miri Yavzori; Ella Fudim; Moran Tardio Duchan; Emad Sakhnini; Alon Lang; Maor Lahav; Talia Saker; Sandra Neuman; et al. (Cancer Medicine)
Abstract Aims and Background Matrix metalloproteinase‐7 (MMP‐7) and Syndecan‐1 (SDC1) are involved in multiple functions during tumorigenesis. We aimed to evaluate the diagnostic and prognostic performance of these serum proteins, as potential biomarkers, in patients with pancreatic ductal adenocarcinoma (PDAC) and benign pancreatic cysts. Methods In this case–control study, patients with newly diagnosed PDAC (N = 121) were compared with the benign cyst (N = 66) and healthy control (N = 48) groups. Serum MMP‐7 and SDC1 were measured by ELISA. The diagnostic accuracy of their levels for diagnosing PDAC and pancreatic cysts was computed, and their association with survival outcomes was evaluated. Results MMP‐7 median serum levels were significantly elevated in the PDAC (7.3 ng/mL) and cyst groups (3.7 ng/mL) compared with controls (2.9 ng/mL) (p < 0.001 and 0.02, respectively), and also between the PDAC and cyst groups (p < 0.001), while SDC1 median serum levels were significantly elevated in PDAC (43.3 ng/mL) compared with either cysts (30.1 ng/mL, p < 0.001) or controls (31.2 ng/mL, p < 0.001). The receiver operating characteristic curve analysis area under the curve in PDAC versus controls was 0.90 and 0.78 for MMP‐7 and SDC1, respectively, while it was 1.0 for the combination of the two and CA 19‐9 (p < 0.001). The combination of the three biomarkers had a perfect sensitivity (100%). Conclusions Due to its high sensitivity, this biomarker panel has the potential to rule out PDAC in suspected cases.